Out of their depth: The successful use of cultured subtidal mussels for intertidal restoration. Issue 4 (9th March 2023) - Toone, Trevyn A.; Hillman, Jenny R.; Benjamin, Emilee D.; Handley, Sean; Jeffs, Andrew
Abstract: Ecosystem restoration has proliferated across the globe to combat widespread ecosystem decline. Translocations of viable individuals into degraded habitats form a core component of restoration efforts, but the selection of source populations poses challenges because phenotypic differences between source populations and depleted populations result in low post‐translocation survival. Intertidal mussel restoration is typically reliant on subtidal source populations despite their weaker shells, lighter weights, and poorer respiratory abilities compared to intertidal mussels. Intertidal mussel restoration using subtidal mussels has recorded very low survival, leading to suggestions that subtidal mussels are unfit for the intertidal zone, effectively eliminating the possibility of translocation‐based intertidal mussel restoration. In this study, small‐scale intertidal mussel restoration was tested using subtidal cultured mussels transplanted to paired plots, half in the lower intertidal and half in the upper subtidal. The results demonstrate the first scientific evidence of the successful restoration of intertidal mussel reefs using subtidal mussels at this scale. Specifically, one location recorded very high survival after 12 months (95.1 ± 0.6%; mean ± SE), comparable to the survival recorded in the subtidal zone (97.6 ± 0.3%). Translocations to the intertidal at the other two locations experienced mortality during the Austral summer (final survival: 81.3 ± 1.6% and 56.6 ± 7.4%), which directly correlated with exposure to extreme temperatures (>40°C). These results reveal that despite phenotypic differences, subtidal cultured mussels are potential sources for successful intertidal restoration. However, care should also be taken to avoid locations prone to high temperatures, particularly in light of a warming global environment. Ultimately, to achieve the massive upscaling in restoration called for by the UN Decade on Ecosystem Restoration, we encourage restoration managers to think broadly about potential source populations, avoid rejections based solely on phenotypic differences, and explore every potential avenue for restoration success. Abstract : We demonstrate for the first time that mussels grown in the subtidal can successfully be transplanted to the intertidal for restoration despite significant phenotypic mismatch. These findings suggest that translocation‐based restoration initiatives may have a wider range of potential source populations than previously considered.